The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/qai.0000000000000178
|View full text |Cite
|
Sign up to set email alerts
|

Effective Approaches for Programming to Reduce Adolescent Vulnerability to HIV Infection, HIV Risk, and HIV-Related Morbidity and Mortality

Abstract: These priority interventions with proven effectiveness should be included in all HIV prevention programming for adolescents. There is a pressing need for more rigorous research on how best to enable adolescents to access these effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 55 publications
2
54
1
Order By: Relevance
“…Yet, young people who have access to care face a host of complex challenges . Existing literature covers the scale of adherence problems in this population (Kim et al 2014;Hudelson and Cluver 2015), interventions to address these (Mavedzenge et al 2014), and caregivers' views about managing young people's knowledge about their HIV status and their adherence to medication (Vreeman et al 2013). Much less is known about young people's own perspectives about growing up with HIV and on ART.…”
mentioning
confidence: 99%
“…Yet, young people who have access to care face a host of complex challenges . Existing literature covers the scale of adherence problems in this population (Kim et al 2014;Hudelson and Cluver 2015), interventions to address these (Mavedzenge et al 2014), and caregivers' views about managing young people's knowledge about their HIV status and their adherence to medication (Vreeman et al 2013). Much less is known about young people's own perspectives about growing up with HIV and on ART.…”
mentioning
confidence: 99%
“…A qualitative study among South African youth (12–24 years) revealed that they felt clinic staff provided inappropriate HIV-testing services for youth [26]. A systematic review of effective approaches to reducing HIV risk among adolescents suggested making health services more youth oriented (including accessible hours, privacy, and staff trained specifically to work with adolescents) [27]. In addition, youth-friendly services may link adolescents to a variety of other adolescent health services [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of successful HIV/STI prevention interventions are based on cognitive and behavioral determinants of sexual risk (Mavedzenge, Luecke, & Ross, 2014). These models may not adequately address the risk mechanisms of adolescents who have psychiatric, cognitive, behavioral, and/or emotional deficits.…”
Section: Hiv/sti Prevention Interventions For Adolescents With Mentalmentioning
confidence: 99%
“…Through rigorous randomized controlled trials, investigators can design and disseminate manualized curricula for comprehensive HIV/STI risk assessment and prevention programs to be delivered in mental health treatment settings. While proven effective programs are available for the general adolescent population, challenges remain in identifying the best ways to help them access these services (Mavedzenge et al, 2014). A variety of inpatient and outpatient treatment settings—including residential treatment programs and day programs—can be targeted to engage youth currently receiving mental health treatment and address their unmet sexual health needs.…”
Section: Integrating Hiv and Mental Health Services For Hiv Preventionmentioning
confidence: 99%